Ground effect for ducted wind turbines: A computational study. Issue 4 (1st May 2022) - Sheshadri, Shraddha M.; Dighe, Vinit V.
Abstract: Ducted wind turbines (DWTs) can take the advantage of ground effect (GE) when installed close to urban areas. To this aim, a parametric study to investigate the aerodynamic performance of DWTs in relation to three different ground distances are investigated. The flow around a commercial DWT model using a simplified duct actuator disc (AD) model based on Reynolds Averaged Navier-Stokes (RANS) equations is performed. The results indicate that DWTs placed close to the ground will lead to increased mass flow rate the turbine plane, and thereby improving the aerodynamic performance. However, the additional ground force leads to an asymmetric flow-field at the turbine plane, which will ultimately induce unsteady forces on the DWT system. The present analysis will serve as a strong recommendation to address siting issues for DWT manufacturers.